The Impact of depreciation of exchange rate toward trade balance in Indonesia - PUTRI, Kusuma Hani (KDI School, 2019)
Currently, the recovering US economy and the raising of protectionism have triggered external shock in several countries including Indonesia. Hence, this study aims to analyze the causalityIbetweenIthe exchangeIrate and theItradeIbalance in Indonesia, to measure and forecast the impact of the depreciation of the exchange rate and trade balance in Indonesia, and to identify ithe impact ofi depreciation of iexchange irate toward Indonesia’s export performance of manufactured, agricultural, and mining commodities. In accordance to achieve the objective of the study, this study use time series analysis. The findings show that the irelationship ibetween itrade ibalance iand iexchange irate in Indonesia is one-way; only ithe iexchange irate affects the trade balance in Indonesia. Furthermore, if there is a shock from the exchange rate, it iwill ilead to a decrease in itradeibalance by about 0.45 percent in 6 months. In the commodity level, agricultural commodity gets higher deterioration compared to manufactured, mining commodity will increase if there is depreciation of the exchange rate. Moreover, J-curve does not exist either at the aggregate level or commodity level in Indonesia.
Thesis(Master) --KDI School:Master of Public Policy,2019